2019
DOI: 10.4236/ojpathology.2019.94009
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer: Epidemiological, Clinical, and Therapeutic Aspects in Pointe Noire (Congo Brazzaville)

Abstract: Introduction: Breast cancer is the leading cancer and the leading cause of cancer death in women worldwide. The objective of our study was to describe the epidemiological, clinical and therapeutic aspects of breast cancer at the General Hospital of Loandjili in Pointe Noire. Patients and Methods: This was a descriptive and cross-sectional study that took place in the Cancer Department of the General Hospital of Loandjili in Pointe Noire during the period from January 1st, 2012 to December 31st, 2016 for durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Numerous studies have shown that early diagnosis of cancer allows effective management at a lower cost and improve the overall survival of patients with breast cancer [ 5 , 6 ]. In Cameroon, due to economic constraints, cultural reasons, the absence of systematic screening policies and also the lack of means of exploration, the management of breast cancer is difficult [ 7 ]. This explains why the overall survival at 5 years in Cameroon was found around 30% between January 1992 and December 2010 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that early diagnosis of cancer allows effective management at a lower cost and improve the overall survival of patients with breast cancer [ 5 , 6 ]. In Cameroon, due to economic constraints, cultural reasons, the absence of systematic screening policies and also the lack of means of exploration, the management of breast cancer is difficult [ 7 ]. This explains why the overall survival at 5 years in Cameroon was found around 30% between January 1992 and December 2010 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%